Development and testing of a system for forming neutron fluxes on a linear electron accelerator - Gokov, S.P.; Horbach, V.M.; Kalenik, S.A.; Kazarinov, Yu.G.; Kantemirov, V.V.; Kasilov, V.I.; Kochetov, S.S.; Lyukhtan, O.A.; Tverdohvalov, A.V.; Tsiats’ko, V.V.; Tsiats’ko, E.V. (Problems of Atomic Science and Technology, 2022)
A system for the formation of neutron fluxes, consisting of a neutron converter, a neutron reflector and a lead protection, has been developed and partially manufactured. Test tubes with an aqueous solution of the organic dye methyl orange with the addition of 4% boric acid were used as detectors of the generated neutron fluxes, which is associated with the impossibility of using gas-discharge neutron counters in the accelerator bunker due to the impact of pulsed electrical noise and gamma-ray flashes. Testing of the neutron flux formation system showed that the neutron flux at the location of the detectors increased by 15%, while the neutron background in the accelerator bunker decreased by 3 times. The conducted studies have shown the effectiveness of using a chemical dosimeter under conditions of intense pulsed neutron fluxes. Розроблена та частково виготовлена система формування нейтронних потоків, яка складається з нейтронного конвертера, відбивача нейтронів та свинцевого захисту. В якості детекторів сформованих потоків нейтронів використовувалися пробірки з водним розчином органічного барвнику метиловий помаранчевий з додаванням 4% борної кислоти, що пов’язано з неможливістю використання газорозрядних лічильників нейтронів у бункері прискорювача через вплив імпульсних електричних перешкод і гамма-спалахів. Тестування системи формування потоку нейтронів показало, що потік нейтронів у місці розташування детекторів збільшився на 15%, а нейтронний фон у бункері прискорювача зменшився в 3 рази. Проведені дослідження показали ефективність використання хімічного дозиметра в умовах інтенсивних імпульсних потоків нейтронів.